IMPLEMENTASI SYARIAT ISLAM SEBAGAI SOLUSI UNTUK MENGATASI KRISIS LINGKUNGAN - Salafudin Salafudin (UIN K.H. Abdurrahman Wahid Pekalongan, 2009)
Multidimensional crisis that happens now needs to be overcome by human being. The root of the crisis is the loss of spiritual values in human civilization. At present, the awareness of returning transcendent values in human life is appeared. These values are manifested in religious teaching that exists in sharī’at. In a row with shumūliyat al-Islam, sharī’at covers various life dimensions. The objective of sharī’at is to manifest peace, just, compatible, harmonious, and welfare life order. So, the implementation of sharī’at is a solution that is needed to be thought to overcome multidimensional crisis that happens now. This article tries to discuss about it.